A Panel VAR Approach of the Relationship among Economic Growth, CO2 Emissions, and Energy Use in the ASEAN-6 Countries - Magazzino, Cosimo (International Journal of Energy Economics and Policy, 2014)
The paper analyses the relationship among economic growth, carbon dioxide emissions, and energy use for six ASEAN countries over the 1971-2007 years. Using a panel VAR technique, a 3-variable VAR is estimated. Empirical findings show that the response of economic growth to energy use is positive and statistically significant. The forecast errors in real per capita GDP are mainly due to uncertainty in GDP itself and energy use emissions. The error variances in the carbon dioxide emissions are sensible to disturbances both in the GDP and in CO2 equations. While the errors in predicting the energy use are sensitive to disturbances in its own equation: after ten steps. Thus, for the estimated sample, these results reinforced the VAR and IRFs analyses, suggesting that for this panel the “growth hypothesis” holds. Keywords: economic growth; CO2 emissions; energy use; ASEAN; panel data JEL Classifications: B22; C33; N55; Q48